Ghostings, materialisations and flows in Britain's special educational needs and disability assemblage. Issue 1 (2nd January 2017) - Allan, Julie; Youdell, Deborah
ABSTRACT: In this paper we argue that the UK government's new special educational needs and disability (SEND) Code of Practice marks a further movement in the expansion of what Tomlinson has identified as the SEN industry. Yet at the same time, we suggest that the Code inaugurates a series of less familiar movements of policy, of governance and responsibility, of understanding SEND, and of the constitution of subjects identified in these terms. We make use of Deleuze's notion of assemblages and societies of control to think about the 'ghostings', 'materialisations' and 'flows' found within the Code and the ways in which these instantiate an 'empty architecture' which education, health and care professionals as well as children, young people and parents/carers must simultaneously furnish and navigate. We examine this new terrain for conceptualising, administering and responding to SEND and suggest that a new orientation to analysis and critique is needed.